ANALISIS HADIS-HADIS TENTANG SOLUSI PERBEDAAN PENDAPAT - Siregar, Dame (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2020)
Dissent unity eventually will be depleted little by little, fraternity will be depleted. Differences of opinion are prohibited from the Qur'an and Sunnah. Solutions dissent is read fiqh books are there, if any argument then the next step please Takhrij Hadith worship in terms of sanad and matannya. If there is already a noble task argument then we next return trackÂ  sanad and the Hadith of as matan. If there are differences of opinion then restore the Qur'an and Sunnah. The aimmatul schools wrote the opinion, because of the limited sunnah they found they were not wrong. Our job resume their message, if there is sunnah that sohih, then resume practicing sunnah that you leave our opinion. Aimmatul the four schools and in others is Sunnah wal Jamaah sect, not a school of their names. If the four schools of Sunnah wal Jamaah sect of course we too should Sunnah wal Jamaah. Finally was reached a people who are united to cling to the Sunnah wal Jamaah, much of the dissent. The motto of dissent is grace neglected, then reached common understanding that grace according to the duties of the Prophet was sent rohmatal lil'alamin.Â